Behavior in reverse: Reasons for return migration - Oded Stark (University of Bonn, Center for Development Research (ZEF), 2018)
Received research shows numerous motives for migration, but fewer reasons for return migration. This paper aims to correct this imbalance. Twelve reasons for return migration are presented and discussed briefly. The reasons listed are derived from research on migration conducted by the author in the course of the past three and a half decades. The purpose of the paper is to pull together the insights gained from that research so as to formulate a base for future inquiry, both analytical and empirical. In addition, just as research on motives for migration can help to establish the reasons for return migration, research on the latter can help to deepen understanding of the former. Moreover, in a great many circumstances and for a variety of reasons, countries that host migrants may want them to leave. In such circumstances, enacting policies that align with motives for return migration will be more efficient than devising measures that are independent of these motives.
Keywords: F22; F24; I31; J61; 330; Reasons for return migration